Role of Saccharomyces cerevisiae Msh2 and Msh3 repair proteins in double-strand break-induced recombination - Sugawara, Neal (The National Academy of Sciences of the USA, 1997)
When gene conversion is initiated by a double-strand break (DSB), any nonhomologous DNA that may be present at the ends must be removed before new DNA synthesis can be initiated. In Saccharomyces cerevisiae, removal of nonhomologous ends depends not only on the nucleotide excision repair endonuclease Rad1/Rad10 but also on Msh2 and Msh3, two proteins that are required to correct mismatched bp. These proteins have no effect when DSB ends are homologous to the donor, either in the kinetics of recombination or in the proportion of gene conversions associated with crossing-over. A second DSB repair pathway, single-strand annealing also requires Rad1/Rad10 and Msh2/Msh3, but reveals a difference in their roles. When the flanking homologous regions that anneal are 205 bp, the requirement for Msh2/Msh3 is as great as for Rad1/Rad10; but when the annealing partners are 1,170 bp, Msh2/Msh3 have little effect, while Rad1/Rad10 are still required. Mismatch repair proteins Msh6, Pms1, and Mlh1 are not required. We suggest Msh2 and Msh3 recognize not only heteroduplex loops and mismatched bp, but also branched DNA structures with a free 3′ tail.